2015
DOI: 10.35790/ecl.3.1.2015.8515
|View full text |Cite
|
Sign up to set email alerts
|

Survei Kesehatan Tenggorokan Di Desa Tinoor Dua

Abstract: Pharyngitis is a common disease in adults and children. Approximately 15-30% of pharyngitis cases occurred in children of school age and 10% of cases in adults. Chronic tonsillitis has the highest prevalence rate according to epidemiological data of ENT disease in seven provinces in Indonesia in 1994-1996. This stuudy aimed to obtain data about the health survey of throat among Tinoor Dua villagers. This study used a descriptive observational method and a cross sectional design. Overview of throat health statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Tonsillitis is common in children but can also affect adults. [1][2][3] From the physical examination, there were signs of chronic inflammation of the palatine tonsils. The tonsil size had enlarged past the tonsillar fossa (T2 / T3), with hyperemic mucosa, as well as dilated crypts but did not appear to be filled with detritus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tonsillitis is common in children but can also affect adults. [1][2][3] From the physical examination, there were signs of chronic inflammation of the palatine tonsils. The tonsil size had enlarged past the tonsillar fossa (T2 / T3), with hyperemic mucosa, as well as dilated crypts but did not appear to be filled with detritus.…”
Section: Discussionmentioning
confidence: 99%
“…These infections can be caused by viruses or bacteria, with the most common are Group-A Beta-hemolytic Streptococcus bacteria. [2][3][4] Chronic tonsillitis is the most common recurrent throat diseases. Epidemiological data showed that 5-15 years old children and adolescents are most often affected by tonsillitis, but it can affect anyone, including adults.…”
Section: Introductionmentioning
confidence: 99%
“…Bakteri yang masuk melalui hidung dan mulut akan disaring oleh Tonsil. 1 Bagian belakang dari rongga mulut dan dinding faring terdapat jaringan limfoid yang terbentuk dari beberapa organ limfatik diantaranya tonsil palatina, tonsil faringeal, tonsil lingual dan tonsil torus tubarius. Struktur limfatik melindungi jalur pernafasan dan saluran pencernaan, yang disebut cincin limfatik faringeal atau waldeyer's ring.…”
Section: Pendahuluanunclassified
“…Paparan ini mungkin menyebabkan estimasi atas pengaruh dari kesehatan pribadi. 3 Siswa sekolah juga rentan terhadap berbagai penyakit, termasuk didalamnya masalah kesehatan tenggorok. Hal ini disebabkan oleh beberapa faktor, diantaranya ialah kebiasaan berbelanja makanan tidak higienis atau makanan yang dapat meningkatkan risiko untuk terjadinya masalah kesehatan tenggorok dan kegiatankegiatan di luar maupun di dalam lingkungan sekolah yang diprogramkan di sekolah-sekolah.…”
unclassified